Calibration and Validation of Analytical Methods - A Sampling of Current Approaches 2018
DOI: 10.5772/intechopen.72932
|View full text |Cite
|
Sign up to set email alerts
|

Linearity of Calibration Curves for Analytical Methods: A Review of Criteria for Assessment of Method Reliability

Abstract: Calibration curve is a regression model used to predict the unknown concentrations of analytes of interest based on the response of the instrument to the known standards. Some statistical analyses are required to choose the best model fitting to the experimental data and also evaluate the linearity and homoscedasticity of the calibration curve. Using an internal standard corrects for the loss of analyte during sample preparation and analysis provided that it is selected appropriately. After the best regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 18 publications
4
99
0
6
Order By: Relevance
“…The bioassay presented a broad linear response from 1 pg mL −1 to 10 µg mL −1 and curve equation of eCL factor = (15.562 ± 0.328) − (0.789 ± 0.042) × Ln(C haptoglobin ). It should be highlighted that the wide range of reference haptoglobin concentrations are prone to heteroscedasticity within semi-logarithmic scale, thus leading to inaccuracy of the calibration [36]. However, herein, the presented correlation coefficient (R 2 = 0.98) depicts sufficient linearity and minimal statistical error deviation of the sampling points (in the range of 0.4%–5.8%).…”
Section: Resultsmentioning
confidence: 81%
“…The bioassay presented a broad linear response from 1 pg mL −1 to 10 µg mL −1 and curve equation of eCL factor = (15.562 ± 0.328) − (0.789 ± 0.042) × Ln(C haptoglobin ). It should be highlighted that the wide range of reference haptoglobin concentrations are prone to heteroscedasticity within semi-logarithmic scale, thus leading to inaccuracy of the calibration [36]. However, herein, the presented correlation coefficient (R 2 = 0.98) depicts sufficient linearity and minimal statistical error deviation of the sampling points (in the range of 0.4%–5.8%).…”
Section: Resultsmentioning
confidence: 81%
“…Furthermore, the spike-and-recovery test was applied to assess accuracy, which was calculated by adding a known amount of analyte to different volumes of pure standard cortisol solution. Only one value did not correspond to the required results: the inter-assay CV of Anas was just above the 15% reference point, from which a non-optimal inter-assay performance can be concluded [63][64][65]. However, in summary, the validation tests confirmed that it is possible to detect corticosterone concentrations in feathers of Anser and Anas with an acceptable repeatability and reliability by using ELISA.…”
Section: Discussionmentioning
confidence: 91%
“…The acquired concentration curve of A VI confers two messages. First, since A VI is not proportional to C VI , as shown in Figure 2 , traditional methods are not applicable 49 for the quantitative analysis of Cr(VI) in water based on its detected SERS signal. Second, the effective concentration range of SERS detection is roughly between 0.1 and 2 mg/L.…”
Section: Resultsmentioning
confidence: 99%